2020
DOI: 10.2147/tcrm.s242952
|View full text |Cite
|
Sign up to set email alerts
|

<p>Trans-Cricothyroid Membrane Injection of Local Anesthesia Attenuates Cough Response and Postoperative Sore Throat to the Nasotracheal Tube</p>

Abstract: Objective: This study aims to investigate the effects of trans-cricothyroid membrane injection of local anesthesia on cough response and postoperative sore throat to the nasotracheal tube. Methods: Patients who require general anesthesia with nasotracheal tube for oral and maxillofacial surgery were randomised divided into groups L and C. The patients in group L received trans-cricothyroid membrane injection of 2% lidocaine (3 mL) before anesthesia. Meanwhile, the same volume of 0.9% saline was administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…indicated that the incidence of agitation was nearly 65% after ap reconstruction [4,5]. These adverse events are related to activation of the sympathetic nervous system that manifests with serious cardiovascular responses, and severe agitation can lead to self-harm, failure of the transferred ap and greatly affect the patient's rehabilitation [3,4,16]. It's essential to take effective anesthetic to make the patient awake smoothly from general anesthesia and keep a well sedated state after ap surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…indicated that the incidence of agitation was nearly 65% after ap reconstruction [4,5]. These adverse events are related to activation of the sympathetic nervous system that manifests with serious cardiovascular responses, and severe agitation can lead to self-harm, failure of the transferred ap and greatly affect the patient's rehabilitation [3,4,16]. It's essential to take effective anesthetic to make the patient awake smoothly from general anesthesia and keep a well sedated state after ap surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at present, more and more patients kept tracheal catheter after ap surgery instead of tracheotomy with the rapid development of oral and maxillofacial ICU. However, the tracheal tube is a strong irritation and could increase postoperative cough response and agitation, which not only cause acute hemodynamic changes and failure of the transferred ap, but also signi cantly delay the patient's rehabilitation [3,4]. Allak et al indicated that agitation occurs in nearly 65% of patients after ap reconstruction [5].…”
Section: Introductionmentioning
confidence: 99%